agroforestry in dryland africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Agriculture in Vanuatu A Historical Review' by Parry Weightman, 1989, ISBN 0 0514377 0 4, price UKL10 softback, available from The British Friends of Vanuatu -67 Beresford Road Cheam - Surrey SM2 6ER - UK Published with the help of funds from ODA,...